Intergenerational effects of environmentally-aged microplastics on the Crassostrea gigas. (1st February 2022) - Bringer, Arno; Cachot, Jérôme; Dubillot, Emmanuel; Prunier, Grégoire; Huet, Valérie; Clérandeau, Christelle; Evin, Louise; Thomas, Hélène
Abstract: This study focused on the impacts of aged aquaculture microplastics (MPs) on oysters ( Crassostrea gigas ). Adult oysters were exposed for two months to a cocktail of MPs representative of the contamination of the Pertuis Charentais area (Bay of Biscay, France) and issuing from oyster framing material. The MPs mixture included 28% of polyethylene, 40% of polypropylene and 32% of PVC (polyvinyl chloride). During the exposure, tissues were sampled for various analyzes (MP quantification, toxicity biomarkers). Although no effect on the growth of adult oysters was noted, the mortality rate of bivalves exposed to MPs (0.1 and 10 mg. L −1 MP) increased significantly (respectively 13.3 and 23.3% of mortalities cumulative). On the one hand, the responses of biomarkers revealed impacts on oxidative stress, lipid peroxidation and environmental stress. At 56 days of exposure, significant increases were noted for Glutathione S-Transferase (GST, 10 mg. L −1 MP), Malondialdehyde (MDA, 10 mg. L −1 MP) and Laccase (LAC, 0.1 and 10 mg. L −1 MP). No variations were observed for Superoxyde Dismutase (SOD). Besides, ingestion of MPs in oyster tissues and the presence in biodeposits was highlighted. In addition, in vitro fertilisations were performed to characterize MPs effects on the offspring. Swimming behavior, development and growth of D-larvae were analysed at 24-, 48- and 72-h after fertilisation. D-larvae, from exposed parents, demonstrated reduced locomotor activity. Developmental abnormalities and arrest as well as growth retardation were also noted. This study highlighted direct and intergenerational effects of MPs from aged plastic materials on Pacific oysters. Graphical abstract: Image 1 Highlights: Oyster adults were exposed for 2 months to microplastics (MPs) aged cocktail. MPs affected survival and modulated certain toxicity biomarkers. MPs were quantified in the tissues and faeces of exposed oysters. The larval offspring was impacted on swimming activity, development and growth.